Battery diaphragm as well as preparation method and application thereof
The lithium battery separator is coated with thienyl polyamide coating solution, and the existing separator has solved the problems of high heat shrinkage and poor adhesion, and achieved a lithium battery separator with low heat shrinkage, good wetting and safety, which has green and environmentally friendly characteristics.
Patent Information
- Application Number
- CN202511055373.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-30
- Publication Date
- 2025-08-29
- Estimated Expiration
- 2045-07-30
AI Technical Summary
The existing lithium battery separators have problems such as high heat shrinkage, low film rupture temperature and low lithium ion transmission efficiency, and the existing coating materials have problems such as high cost, poor adhesion and insufficient safety.
Using a thienyl polyamide coating solution, a lithium battery separator with high bonding ability and heat resistance is formed by mixing organic solvents, thienyl polyamides, nanoceramic particles, emulsifiers and adhesive A.
The prepared lithium battery separators have low heat shrinkage, good wetting and improved safety. At the same time, the materials are easy to obtain, green and environmentally friendly, and are suitable for large-scale industrial production.
Smart Images

Figure CN120565995A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a battery separator and a preparation method and application thereof. Background Art
[0002] Lithium batteries, with their high energy density and long cycle efficiency, are increasingly in demand in the new energy sector. Lithium battery separators are a key component of lithium batteries and play a vital role in battery safety.
[0003] Polyolefin separators are currently the most widely used separators for lithium-ion batteries. However, due to the inherent properties of the material and the limitations of the preparation process, polyolefin separators suffer from problems such as excessive thermal shrinkage, low membrane rupture temperature, and low lithium-ion transmission efficiency. Currently, polyethylene and polypropylene separators are the most widely used, but these two materials soften and deform at around 120°C, resulting in certain limitations in battery safety. To improve the heat resistance and wettability of polyolefin separators, the main approach currently is to coat the surface of the polyolefin separator with inorganic or organic substances, such as ceramic coatings or PVDF and aramid coatings. Ceramic or PVDF coatings have very limited improvements in thermal performance; the aramid coating process is prone to gelation, short raw material shelf life, low processing yield, weak adhesion of the separator coating, and easy powdering and shedding, causing battery safety accidents.
[0004] In order to solve the performance defects of the diaphragm and meet the needs of low-carbon green development, it is of great significance to develop bio-based organic coating materials with good thermal stability and high mechanical properties. Summary of the Invention
[0005] The present invention aims to address the performance deficiencies of polyolefin lithium battery separators in the prior art, thereby providing a battery separator, preparation method, and application thereof. The battery separator utilizes thiophene-based polyamide in the field of lithium battery separators, resulting in a coated lithium battery separator having the advantages of low thermal shrinkage and good wettability. Adhesive A is also used to enhance the bonding ability of the battery separator. Furthermore, due to the inherent adhesive properties of polyamide, which possesses high strength and heat resistance, the coated lithium battery separator also exhibits improved safety. Furthermore, the thiophene-based polyamide coating solution of the present invention has simple and readily available raw materials, an easy-to-use preparation method, low cost, and is environmentally friendly, offering broad application prospects.
[0006] In order to achieve the above objectives, in a first aspect, the present invention provides a method for preparing a thiophene-based polyamide coating liquid, the preparation method comprising: first mixing an organic solvent with thiophene-based polyamide, and then adding nano-ceramic particles, an emulsifier and an adhesive for second mixing.
[0007] Furthermore, the thienyl polyamide is composed of a dibasic acid chloride monomer and a diamine monomer.
[0008] Furthermore, the dicarboxylic acid chloride monomer is selected from one or two or more of thiophene dicarboxylic acid chloride, a copolymerization monomer consisting of thiophene dicarboxylic acid chloride and an aromatic dicarboxylic acid chloride, a copolymerization monomer consisting of thiophene dicarboxylic acid chloride and a heterocyclic dicarboxylic acid chloride, and a copolymerization monomer consisting of thiophene dicarboxylic acid chloride and an aliphatic dicarboxylic acid chloride; and the diamine monomer is selected from one or two or more of aromatic diamine, aliphatic diamine, and heterocyclic diamine.
[0009] Furthermore, the dibasic acid chloride monomer is selected from one or two or more of naphthalene dicarboxylic acid chloride, isophthaloyl chloride, 1,3,5-benzene trimethylenedicarboxylic acid chloride, 2,5-furan dicarboxylic acid chloride, terephthaloyl chloride, piperidine dicarboxylic acid chloride and pyridine dicarboxylic acid chloride.
[0010] Furthermore, the diamine monomer is selected from one or two or more of 2-(4-aminophenyl)-5-aminobenzoxazole, 4,4'-(1,4-phenylenedioxy)dianiline, 2-(4-aminophenyl)-5-aminobenzimidazole, 3,4-diaminodiphenyl ether, butanediamine, pentamethylenediamine, hexamethylenediamine, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3-diaminodiphenyl sulfone, m-phenylenediamine, 9,9-bis(4-aminophenyl)fluorene, naphthalenediamine, p-phenylenediamine, 4,4-diaminodiphenyl ether, 2,2'-bis(trifluoromethyl)diaminobiphenyl, 4,4-diaminodiphenyl sulfone, ethylenediamine, propylenediamine, nonanediamine, 4,4'-bis-3-aminophenoxydiphenyl sulfone and 2,2'-bis[4-(4-aminophenoxyphenyl)]propane.
[0011] Furthermore, the general structural formula of the thiophene-based polyamide is shown in Formula I to Formula VI. , , , , , ; in, X and Y are each independently selected from one of H, an alkyl group, a halogen atom, an amino group, an amino derivative group, a hydroxyl group, and a hydroxyl derivative group; m ≥ 1 and is an integer, h ≥ 1 and is an integer, n ≥ 1 and is an integer, k ≥ 1 and is an integer; R', R" and R'" are each independently selected from one of an alkyl group, a phenyl group, a bridged ring group, a spiro ring group and a heterocyclic group.
[0012] Furthermore, the organic solvent is selected from one or two or more of N-methylpyrrolidone, N-ethylpyrrolidone, γ-valerolactone, γ-butyrolactone, N,N-dimethylformamide, N,N-dimethylacetamide and ethylene glycol dimethyl ether.
[0013] Furthermore, the emulsifier is selected from one or two or more of sodium thiophenedicarboxylate, sodium succinate, sodium p-toluenesulfonate, lithium succinate, lithium p-toluenesulfonate and sodium dodecylsulfonate.
[0014] Furthermore, the adhesive is selected from one or two or more of adhesive A, a mixture of adhesive A and PVDF, a mixture of adhesive A and copolymerized vinyl acetate, and a mixture of adhesive A and styrene-butadiene rubber.
[0015] Furthermore, the nano-ceramic particles are selected from one or two or more of aluminum oxide, magnesium oxide, zinc oxide, aluminum hydroxide and silicon dioxide.
[0016] Furthermore, the particle size of the nano-ceramic particles is 300-500 nm.
[0017] Furthermore, the weight proportions of the organic solvent, thiophene polyamide, nano-ceramic particles, emulsifier and adhesive are as follows: 6-30 parts of thiophene polyamide, 50-150 parts of organic solvent, 10-30 parts of the nano-ceramic particles, 2-10 parts of emulsifier and 1-10 parts of adhesive.
[0018] Furthermore, the first mixing conditions include: temperature of 15-30° C., time of 0.5-2 h, and stirring rate of 150-300 rpm.
[0019] Furthermore, the second mixing conditions include: temperature of 15-30° C., time of 1-3 h, and stirring rate of 150-300 rpm.
[0020] Furthermore, the adhesive A is a polyarylene olefin carboxylate zinc salt composed of a first monomer, a second monomer and zinc hydroxide.
[0021] Furthermore, the structural formula of the first monomer is shown in formula (a): ; The second monomer is butadiene.
[0022] Furthermore, the preparation method of the adhesive A includes: 1) mixing a first monomer with zinc hydroxide in the presence of a first solvent, reacting the mixture, performing distillation under reduced pressure, and drying to obtain a zinc carboxylate salt of the first monomer; 2) mixing the zinc carboxylate salt of the first monomer obtained in step 1) with the second monomer in the presence of a second solvent, and then adding tetramethylethylenediamine and n-butyllithium to initiate polymerization; Wherein, the structural formula of the first monomer is shown as formula (a): ; The second monomer is butadiene.
[0023] Furthermore, in step 1), the first solvent is a mixed solution of ethanol and water, and the mass ratio of ethanol to water is 1-2:1.
[0024] Furthermore, in step 1), the mixing reaction conditions include: temperature of 40-60° C. and time of 1-3 h.
[0025] Furthermore, in step 1), the mass ratio of the first monomer to zinc hydroxide is 1:0.2-0.6.
[0026] Furthermore, in step 2), the second solvent is tetrahydrofuran.
[0027] Furthermore, in step 2), the mass ratio of the zinc salt of the carboxylate of the first monomer to the second monomer is 1:0.2-0.6.
[0028] Furthermore, in step 2), the mixing conditions include: under anaerobic conditions, a stirring rate of 150-300 rpm, and a temperature of 40-50°C.
[0029] Furthermore, in step 2), 5-10 mmol of tetramethylethylenediamine and 5-10 mmol of n-butyllithium are added per 100 g of butadiene.
[0030] Furthermore, in step 2), the polymerization conditions include: under nitrogen atmosphere and / or argon atmosphere, the polymerization temperature is 30-60° C., and the time is 4-8 hours.
[0031] In a second aspect, the present invention provides an application of a thiophene-based polyamide coating liquid in preparing a lithium battery separator, wherein the thiophene-based polyamide coating liquid is the thiophene-based polyamide coating liquid prepared by the preparation method described in the first aspect.
[0032] In a third aspect, the present invention provides a method for preparing a lithium battery separator, the method comprising: applying a thiophene-based polyamide coating liquid to one or both sides of a base film, performing coagulation bath extraction, and drying; wherein, The thiophene-based polyamide coating liquid is the thiophene-based polyamide coating liquid prepared by the preparation method described in the first aspect; The coating thickness is 0.5-4 μm; The base film is a polyethylene base film or a polypropylene base film.
[0033] In the above technical solution, the thiophene-based polyamide coating solution of the present invention comprises only an organic solvent, thiophene-based polyamide, an emulsifier, and an adhesive, resulting in a simple composition and low cost. Furthermore, thiophene-based polyamide is a bio-based material with a wide range of raw material sources, sustainable and renewable, and environmentally friendly. Furthermore, the lithium battery separator prepared with the thiophene-based polyamide coating solution of the present invention has the advantages of low thermal shrinkage and good wettability. Furthermore, the inherent adhesive properties of thiophene-based polyamide provide enhanced safety.
[0034] Furthermore, the thiophene-based polyamide coating liquid of the present invention uses adhesive A, which introduces carboxyl groups into its structure. The carboxyl oxygen forms hydrogen bonds with the amide bonds of the thiophene-based polyamide, thereby enhancing the binding force. The carboxyl group has a large polarity, thereby enhancing the binding force with the base membrane. Adhesive A also has good heat resistance and higher strength because it introduces zinc metal elements into its structure. The introduction of inorganic substances enhances its rigidity and hardness, thereby making the size of the diaphragm more stable. At the same time, the zinc element and the thiophene ring sulfur element form a strong binding force through covalent bonds and coordination bonds, and strong adhesion is generated between adhesive A and the thiophene polyamide and the base membrane. Adhesive A has a good bonding effect. It acts as a bridge, bonding the base membrane on the one hand and the thiophene-based polyamide on the other hand, so that the coating liquid is more firmly bonded to the base membrane, thereby improving the safety of the battery.
[0035] At the same time, the thiophene-based polyamide coating liquid of the present invention has simple preparation steps, mild reaction conditions, low cost and is green and environmentally friendly, is suitable for industrial mass production, and has broad application prospects.
[0036] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following detailed description, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings: Figure 1 is the NMR image of compound 3 of the present invention; Figure 2 is the NMR image of compound 4 of the present invention; Figure 3 is the NMR image of compound 7 of the present invention; Figure 4 is the NMR spectrum of compound 10 of the present invention. DETAILED DESCRIPTION
[0038] The following is a detailed description of the specific embodiments of the present invention. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not intended to limit the present invention.
[0039] The endpoints of the ranges and any values disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.
[0040] In a first aspect, the present invention provides a method for preparing a thiophene-based polyamide coating liquid, the preparation method comprising: first mixing an organic solvent with thiophene-based polyamide, and then adding nano-ceramic particles, an emulsifier, and an adhesive for second mixing.
[0041] The thiophene-based polyamide coating solution of the present invention comprises only an organic solvent, thiophene-based polyamide, an emulsifier, and an adhesive, resulting in a simple composition and low cost. Furthermore, thiophene-based polyamide is a bio-based material with a wide range of raw material sources, sustainable and renewable, and environmentally friendly. Furthermore, the lithium battery separator prepared using the thiophene-based polyamide coating solution of the present invention exhibits low thermal shrinkage and good wettability. Furthermore, the inherent adhesive properties of thiophene-based polyamide provide enhanced safety.
[0042] In a preferred embodiment of the present invention, the thienyl polyamide is composed of a dibasic acid chloride monomer and a diamine monomer.
[0043] In a preferred embodiment of the present invention, the molar ratio of the diacyl chloride monomer to the diamine monomer is 1:1.
[0044] In a preferred embodiment of the present invention, the dibasic acid chloride monomer is selected from one or two or more of thiophene dicarboxylic acid chloride, a copolymerization monomer consisting of thiophene dicarboxylic acid chloride and an aromatic dicarboxylic acid chloride, a copolymerization monomer consisting of thiophene dicarboxylic acid chloride and a heterocyclic dicarboxylic acid chloride, and a copolymerization monomer consisting of thiophene dicarboxylic acid chloride and an aliphatic dicarboxylic acid chloride.
[0045] In a preferred embodiment of the present invention, the diamine monomer is selected from one or two or more of aromatic diamines, aliphatic diamines and heterocyclic diamines.
[0046] In a preferred embodiment of the present invention, the dibasic acid chloride monomer is selected from one or two or more of naphthalene dicarboxylic acid chloride, isophthaloyl chloride, 1,3,5-benzene trimethylenedicarboxylic acid chloride, 2,5-furan dicarboxylic acid chloride, terephthaloyl chloride, piperidine dicarboxylic acid chloride and pyridine dicarboxylic acid chloride.
[0047] In a preferred embodiment of the present invention, the diamine monomer is selected from one or two or more of 2-(4-aminophenyl)-5-aminobenzoxazole, 4,4'-(1,4-phenylenedioxy)dianiline, 2-(4-aminophenyl)-5-aminobenzimidazole, 3,4-diaminodiphenyl ether, butanediamine, pentamethylenediamine, hexamethylenediamine, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3-diaminodiphenyl sulfone, m-phenylenediamine, 9,9-bis(4-aminophenyl)fluorene, naphthalenediamine, p-phenylenediamine, 4,4-diaminodiphenyl ether, 2,2'-bis(trifluoromethyl)diaminobiphenyl, 4,4-diaminodiphenyl sulfone, ethylenediamine, propylenediamine, nonanediamine, 4,4'-bis-3-aminophenoxydiphenyl sulfone and 2,2'-bis[4-(4-aminophenoxyphenyl)]propane.
[0048] In a preferred embodiment of the present invention, the general structural formula of the thiophene-based polyamide is as shown in Formula I to Formula VI, , , , , , ; in, X and Y are each independently selected from one of H, an alkyl group, a halogen atom, an amino group, an amino derivative group, a hydroxyl group, and a hydroxyl derivative group; m ≥ 1 and is an integer, h ≥ 1 and is an integer, n ≥ 1 and is an integer, k ≥ 1 and is an integer; R', R" and R'" are each independently selected from one of an alkyl group, a phenyl group, a bridged ring group, a spiro ring group and a heterocyclic group.
[0049] In a preferred embodiment of the present invention, the organic solvent is selected from one or two or more of N-methylpyrrolidone, N-ethylpyrrolidone, γ-valerolactone, γ-butyrolactone, N,N-dimethylformamide, N,N-dimethylacetamide and ethylene glycol dimethyl ether.
[0050] In a preferred embodiment of the present invention, the emulsifier is selected from one or two or more of sodium thiophenedicarboxylate, sodium succinate, sodium p-toluenesulfonate, lithium succinate, lithium p-toluenesulfonate and sodium dodecylsulfonate.
[0051] In a preferred embodiment of the present invention, the adhesive is selected from one or two or more of adhesive A, a mixture of adhesive A and PVDF, a mixture of adhesive A and copolyvinyl acetate, and a mixture of adhesive A and styrene-butadiene rubber.
[0052] In a preferred embodiment of the present invention, the nano-ceramic particles are selected from one or two or more of aluminum oxide, magnesium oxide, zinc oxide, aluminum hydroxide and silicon dioxide.
[0053] In a preferred embodiment of the present invention, the particle size of the nano-ceramic particles is 300-500 nm.
[0054] In a preferred embodiment of the present invention, the weight ratios of the organic solvent, thiophene polyamide, nano-ceramic particles, emulsifier and adhesive are as follows: 6 to 30 parts of thiophene polyamide, 50 to 150 parts of organic solvent, 10 to 30 parts of the nano-ceramic particles, 2 to 10 parts of emulsifier and 1 to 10 parts of adhesive. For example, the weight ratios are 6 parts of thiophene polyamide, 50 parts of organic solvent, 10 parts of the nano-ceramic particles, 2 parts of emulsifier and 10 parts of adhesive; 10 parts of thiophene polyamide, 80 parts of organic solvent, 15 parts of the nano-ceramic particles, 5 parts of emulsifier and 15 parts of adhesive; 20 parts of thiophene polyamide, 100 parts of organic solvent, 20 parts of the nano-ceramic particles, 8 parts of emulsifier and 2 parts of adhesive, etc.
[0055] In a preferred embodiment of the present invention, the first mixing conditions include: temperature of 15-30° C., time of 0.5-2 h, and stirring rate of 150-300 rpm.
[0056] In a preferred embodiment of the present invention, the second mixing conditions include: temperature of 15-30° C., time of 1-3 h, and stirring rate of 150-300 rpm.
[0057] In a preferred embodiment of the present invention, Adhesive A is a polyarylene olefin carboxylate zinc salt composed of a first monomer, a second monomer, and zinc hydroxide. Compared to conventional adhesives, Adhesive A exhibits higher heat resistance and strength because it incorporates zinc metal into its structure. The addition of inorganic materials enhances its rigidity and hardness, resulting in greater dimensional stability.
[0058] In a preferred embodiment of the present invention, the structural formula of the first monomer is as shown in formula (a): ; The second monomer is butadiene; the adhesive A introduces a carboxyl group into the structure, so that the carboxyl oxygen forms a hydrogen bond with the amide bond of the thiophene polyamide, thereby enhancing the bonding strength; the carboxyl group has a high polarity, thereby enhancing the bonding strength with the base film.
[0059] The adhesive A used in the present invention plays the role of a bridge, bonding the base film on one hand and the thiophene-based polyamide on the other hand, making the bonding between the two stronger and improving the safety performance of the battery.
[0060] In a preferred embodiment of the present invention, the preparation method of the adhesive A comprises: 1) mixing a first monomer with zinc hydroxide in the presence of a first solvent, reacting the mixture, performing distillation under reduced pressure, and drying to obtain a zinc carboxylate salt of the first monomer; 2) mixing the zinc carboxylate salt of the first monomer obtained in step 1) with the second monomer in the presence of a second solvent, and then adding tetramethylethylenediamine and n-butyllithium to initiate polymerization; Wherein, the structural formula of the first monomer is shown as formula (a): ; The second monomer is butadiene.
[0061] In a preferred embodiment of the present invention, in step 1), the first solvent is a mixed solution of ethanol and water, and the mass ratio of ethanol to water is 1 to 2:1, preferably 2:1.
[0062] In a preferred embodiment of the present invention, in step 1), the conditions of the mixing reaction include: a temperature of 40-60° C. and a time of 1-3 h, for example.
[0063] In a preferred embodiment of the present invention, in step 1), the mass ratio of the first monomer to zinc hydroxide is 1:0.2-0.6, for example, 1:0.2, 1:0.3, 1:0.4, 1:0.5 and 1:0.6.
[0064] In a preferred embodiment of the present invention, in step 2), the second solvent is tetrahydrofuran.
[0065] In a preferred embodiment of the present invention, in step 2), the mass ratio of the zinc salt of the carboxylate of the first monomer to the second monomer is 1:0.2-0.6, for example, 1:0.2, 1:0.3, 1:0.4, 1:0.5 and 1:0.6.
[0066] In a preferred embodiment of the present invention, in step 2), the mixing conditions include: under anaerobic conditions, a stirring rate of 150-300 rpm, and a temperature of 40-50°C.
[0067] In a preferred embodiment of the present invention, in step 2), 5-10 mmol tetramethylethylenediamine and 5-10 mmol n-butyllithium are added per 100 g of butadiene. Preferably, 8 mmol tetramethylethylenediamine and 8 mmol n-butyllithium are added per 100 g of butadiene.
[0068] In a preferred embodiment of the present invention, in step 2), the polymerization conditions include: under nitrogen atmosphere and / or argon atmosphere, the polymerization temperature is 30-60° C., and the time is 4-8 hours.
[0069] In a second aspect, the present invention provides an application of a thiophene-based polyamide coating liquid in preparing a lithium battery separator, wherein the thiophene-based polyamide coating liquid is the thiophene-based polyamide coating liquid prepared by the preparation method described in the first aspect.
[0070] In a third aspect, the present invention provides a method for preparing a lithium battery separator, the method comprising: applying a thiophene-based polyamide coating liquid to one or both sides of a base film, performing coagulation bath extraction, and drying; wherein, The thiophene-based polyamide coating liquid is the thiophene-based polyamide coating liquid prepared by the preparation method described in the first aspect; The coating thickness is 0.5-4 μm; The base film is a polyethylene base film or a polypropylene base film.
[0071] The present invention applies thiophene-based polyamide to the field of lithium battery separators. The thiophene-based lithium battery separator prepared using a thiophene-based polyamide coating liquid exhibits low thermal shrinkage, excellent wettability, and inherent adhesion, resulting in improved safety compared to traditional separators. Furthermore, the thiophene-based polyamide coating liquid disclosed in the present invention has a simple composition, resolving the issues of high costs and complex ingredients encountered in existing separator coating technologies. Furthermore, thiophene-based polyamide is a bio-based material with a wide range of sustainable and renewable raw material sources, making it environmentally friendly.
[0072] In the present invention, the room temperature is 15-30°C.
[0073] The present invention will be described in detail below by way of examples. In the following examples, the drugs and pharmaceuticals are all conventional commercial products.
[0074] Preparation Example 1 This preparation example is used to illustrate the preparation of Adhesive A: (1) Add 1 kg of water and 2 kg of ethanol to the reactor, add 100 g of the first monomer, add 40 g of zinc hydroxide, and react at 50 ° C for 2 hours; distill and dry the solvent under reduced pressure (50 ° C, 5 mmHg) to obtain the carboxylic acid zinc salt of the first monomer.
[0075] (2) 50 g of the zinc salt of the carboxylate of the first monomer and 300 ml of tetrahydrofuran were added to the polymerization bottle in sequence and stirred. 20 g of butadiene was added under anaerobic conditions and heated to 45 °C. 0.2 g of tetramethylethylenediamine (TMEDA) and 0.8 mL of n-butyllithium (2.0 mol / L, cyclohexane solution) were added to initiate polymerization. After 5 h of polymerization, 5 ml of ethanol was used to terminate the polymerization. The polymer solution was poured into water to precipitate the solid, which was filtered and the filter cake was dried at 40 °C to obtain Adhesive A.
[0076] Wherein, the structural formula of the first monomer is shown in formula (a):
[0077] Preparation Example 2 This preparation example is used to illustrate the preparation of compound 1-12: Under nitrogen protection, 100 g of DMAC was added first, followed by the diamine monomer. At 5° C., the diacyl chloride monomer was added and reacted for 2 hours. 100 ml of ethanol was added to precipitate the solid, which was filtered and the filter cake was dried to obtain a thienyl polyamide solid, namely compound 1-12.
[0078] The types and amounts of monomers used in compounds 1-12 are shown in Table 1.
[0079] Table 1
[0080] Example 1 100 g of N,N-dimethylformamide (an organic solvent) and 18 g of thiophene polyamide (Compound 1) were added to the reactor in sequence and stirred for 1 hour. Then, 16 g of aluminum oxide, 2 g of adhesive A, and 5 g of sodium p-toluenesulfonate were added and stirred for 2 hours to prepare a thiophene polyamide coating liquid.
[0081] Example 2 100 g of N,N-dimethylformamide (an organic solvent) and 18 g of thiophene polyamide (Compound 2) were added to the reactor in sequence and stirred for 1 hour. Then, 16 g of aluminum oxide, 2 g of adhesive A, and 5 g of sodium p-toluenesulfonate were added and stirred for 2 hours to prepare a thiophene polyamide coating liquid.
[0082] Example 3 100 g of N,N-dimethylformamide (an organic solvent) and 18 g of thiophene polyamide (Compound 3) were added to the reactor in sequence and stirred for 1 hour. 16 g of aluminum oxide, 2 g of adhesive A, and 5 g of sodium p-toluenesulfonate were then added and stirred for another 2 hours to prepare a thiophene polyamide coating liquid. Among them, compound 3 is a polymer of 31.3 g of thiophenedicarboxylic acid chloride and 30 g of 4,4-diaminodiphenyl ether.
[0083] Example 4 100 g of organic solvent N,N-dimethylformamide and 18 g of thiophene polyamide (Compound 4) were added to the reactor in sequence and stirred for 1 hour. Then, 16 g of aluminum oxide, 2 g of adhesive A, and 5 g of sodium p-toluenesulfonate were added and stirred for 2 hours to prepare a thiophene polyamide coating liquid.
[0084] Example 5 100 g of N,N-dimethylformamide (an organic solvent) and 18 g of thiophene polyamide (Compound 5) were added to the reactor in sequence and stirred for 1 hour. Then, 16 g of aluminum oxide, 2 g of adhesive A, and 5 g of sodium p-toluenesulfonate were added and stirred for 2 hours to prepare a thiophene polyamide coating liquid.
[0085] Example 6 100 g of N,N-dimethylformamide (an organic solvent) and 18 g of thiophene polyamide (Compound 6) were added to the reactor in sequence and stirred for 1 hour. Then, 16 g of aluminum oxide, 2 g of adhesive A, and 5 g of sodium p-toluenesulfonate were added and stirred for 2 hours to prepare a thiophene polyamide coating liquid.
[0086] Example 7 100 g of N,N-dimethylformamide (an organic solvent) and 18 g of thiophene polyamide (Compound 7) were added to the reactor in sequence and stirred for 1 hour. Then, 16 g of aluminum oxide, 2 g of adhesive A, and 33 g of sodium p-toluenesulfonate were added and stirred for 2 hours to prepare a thiophene polyamide coating liquid.
[0087] Example 8 100 g of N,N-dimethylformamide (an organic solvent) and 18 g of thiophene polyamide (Compound 8) were added to the reactor in sequence and stirred for 1 hour. Then, 16 g of aluminum oxide, 5 g of sodium p-benzenesulfonate, and 2 g of adhesive A were added and stirred for 2 hours to prepare a thiophene polyamide coating liquid.
[0088] Example 9 100 g of N,N-dimethylformamide (an organic solvent) and 18 g of thiophene polyamide (Compound 9) were added to the reactor in sequence and stirred for 1 hour. Then, 16 g of aluminum oxide, 2 g of adhesive A, and 5 g of sodium p-toluenesulfonate were added and stirred for 2 hours to prepare a thiophene polyamide coating liquid.
[0089] Example 10 100 g of organic solvent N,N-dimethylformamide, 2 g of adhesive A, and 18 g of thiophene polyamide (Compound 10) were added to the reactor in sequence and stirred for 1 hour. Then, 16 g of aluminum oxide and 5 g of sodium p-toluenesulfonate were added and stirred for 2 hours to prepare a thiophene polyamide coating liquid.
[0090] Example 11 100 g of N,N-dimethylformamide (an organic solvent) and 18 g of thiophene polyamide (Compound 11) were added to the reactor in sequence and stirred for 1 hour. Then, 16 g of aluminum oxide, 2 g of adhesive A, 4 g of sodium p-benzenesulfonate, and 1 g of copolymerized vinyl acetate were added and stirred for 2 hours to prepare a thiophene polyamide coating liquid.
[0091] Example 12 100 g of N,N-dimethylformamide (an organic solvent) and 18 g of thiophene polyamide (Compound 12) were added to the reactor in sequence and stirred for 1 hour. Then, 16 g of aluminum oxide, 2 g of adhesive A, and 5 g of sodium p-toluenesulfonate were added and stirred for 2 hours to prepare a thiophene polyamide coating liquid.
[0092] Example 13 100 g of organic solvent N,N-dimethylformamide, 9 g of thienyl polyamide (Compound 5), and 9 g of polyvinylidene fluoride (PVDF) were added to the reactor in sequence and stirred for 1 hour. Then, 16 g of aluminum oxide, 20 g of adhesive A, and 5 g of sodium p-toluenesulfonate were added and stirred for 2 hours to prepare a thienyl polyamide coating liquid.
[0093] Comparative Example 1 The coating liquid was prepared according to the method described in Example 5, except that no thiophene polyamide was added.
[0094] Comparative Example 2 The method described in Example 5 was followed, except that "2 g of adhesive A" was replaced with "2 g of PVDF" to prepare a coating solution.
[0095] Comparative Example 3 The coating liquid was prepared according to the method described in Example 5, except that "20 g of adhesive A" was not added.
[0096] Application Example 1 A polyethylene base film with a thickness of 10 μm was selected, and the thiophene-based polyamide coating liquid prepared in Examples 1-13 and the coating liquid prepared in Comparative Examples 1-2 were respectively coated on both sides of the base film with a coating thickness of 1 μm. The film was extracted in a coagulation bath and dried to obtain a lithium battery separator.
[0097] Test Example 1 The performance test methods and standards for the lithium battery separators coated with the thiophene-based polyamide coating solutions prepared in Examples 1-13 and the coating solutions prepared in Comparative Examples 1-2 are as follows: (1) The liquid absorption rate test method refers to the standard QB / T 2303.11-2008 test. The electrolyte solvent is a mixture of ethylene carbonate and dimethyl carbonate, and the mass ratio of the two is 1:1.
[0098] (2) Thermal shrinkage test method: Cut the diaphragm into 10cm×10cm size samples, measure its longitudinal length (MD-1) and transverse length (TD-1) before heating, place it in a vacuum oven and bake it at 150℃ for 1h, take out the diaphragm sample, cool it to room temperature, measure its longitudinal length (MD-2) and transverse length (TD-2) again, and calculate the thermal shrinkage rate y according to the following formula. Y(MD)=(MD1-MD2) / MD1×100% Y(TD)=(TD1-TD2) / TD1×100% (3) Air permeability test method: refer to the national standard GBT36363-2018 standard test; (4) Peel strength method: refer to the national standard GBT36363-2018 standard test; The performance test data of the lithium battery separators coated with the thiophene-based polyamide coating liquids prepared in Examples 1-13 and the coating liquids prepared in Comparative Examples 1-2 are shown in Table 2.
[0099] Table 2
[0100] It can be seen from the data in Table 2 that the lithium battery separators coated with the thiophene-based polyamide coating liquid of Examples 1-13 of the present invention have significantly improved liquid absorption rates, significantly reduced thermal shrinkage rates, and improved air permeability compared to the lithium battery separators coated with the coating liquid of Comparative Example 1 without adding thiophene-based polyamide, indicating that the lithium battery separators coated with the thiophene-based polyamide coating liquid of the present invention have better thermal stability and wettability.
[0101] Furthermore, the peel strength of the lithium battery separator coated with the thiophene-based polyamide coating liquid of Examples 1-13 of the present invention is significantly improved compared with the lithium battery separator coated with the coating liquid of Comparative Example 1 without adding thiophene-based polyamide and binder, indicating that thiophene-based polyamide has adhesive properties and can play a role in bonding ceramics.
[0102] At the same time, it can be seen from the performance data of the membranes of Comparative Example 2 and Example 5 that the lithium battery membrane coated with the thiophene-based polyamide coating liquid prepared with Adhesive A in Example 5 has higher heat resistance and adhesion than the lithium battery membrane coated with the thiophene-based polyamide coating liquid prepared with the commercially available adhesive PVDF in Comparative Example 2.
[0103] At the same time, it can be seen from the performance data of the separators of Comparative Example 3 and Example 5 that the addition of adhesive A can improve the thermal stability and peel strength of the separator.
[0104] In addition, during the experimental process of the present invention, the polymer did not show any gelation phenomenon and was in a uniform and stable solution state, indicating that the stability of the thiophene-based polyamide coating liquid is better than that of the aramid slurry.
[0105] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the scope of protection of the present invention.
[0106] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any appropriate manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0107] In addition, the various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a thiophene-based polyamide coating liquid, characterized in that: The preparation method comprises: first mixing an organic solvent with thiophene-based polyamide, and then adding nano-ceramic particles, an emulsifier and an adhesive for second mixing.
2. The preparation method according to claim 1, characterized in that The thiophene-based polyamide is composed of a dibasic acid chloride monomer and a diamine monomer; wherein, The dibasic acid chloride monomer is selected from one or more of thiophene dicarboxylic acid chloride, a copolymerization monomer consisting of thiophene dicarboxylic acid chloride and an aromatic dicarboxylic acid chloride, a copolymerization monomer consisting of thiophene dicarboxylic acid chloride and a heterocyclic dicarboxylic acid chloride, and a copolymerization monomer consisting of thiophene dicarboxylic acid chloride and an aliphatic dicarboxylic acid chloride; The diamine monomer is selected from one or two or more of aromatic diamines, aliphatic diamines and heterocyclic diamines.
3. The preparation method according to claim 2, characterized in that The dibasic acid chloride monomer is selected from one or two or more of naphthalene dicarboxylic acid chloride, isophthalic acid chloride, 1,3,5-benzene trimeryl chloride, 2,5-furan dicarboxylic acid chloride, terephthalic acid chloride, piperidine dicarboxylic acid chloride and pyridine dicarboxylic acid chloride; The diamine monomer is selected from one or two or more of 2-(4-aminophenyl)-5-aminobenzoxazole, 4,4'-(1,4-phenylenedioxy)dianiline, 2-(4-aminophenyl)-5-aminobenzimidazole, 3,4-diaminodiphenyl ether, butanediamine, pentamethylenediamine, hexamethylenediamine, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3-diaminodiphenyl sulfone, m-phenylenediamine, 9,9-bis(4-aminophenyl)fluorene, naphthalenediamine, p-phenylenediamine, 4,4-diaminodiphenyl ether, 2,2'-bis(trifluoromethyl)diaminobiphenyl, 4,4-diaminodiphenyl sulfone, ethylenediamine, propylenediamine, nonanediamine, 4,4'-bis-3-aminophenoxydiphenyl sulfone and 2,2'-bis[4-(4-aminophenoxyphenyl)]propane.
4. The preparation method according to claim 1, characterized in that The general structural formula of the thiophene-based polyamide is shown in Formula I to Formula VI. , , , , , ; wherein X and Y are each independently selected from one of H, an alkyl group, a halogen atom, an amino group, an amino derivative group, a hydroxyl group, and a hydroxyl derivative group; m ≥ 1 and is an integer, h ≥ 1 and is an integer, n ≥ 1 and is an integer, k ≥ 1 and is an integer; R', R" and R'" are each independently selected from one of an alkyl group, a phenyl group, a bridged ring group, a spiro ring group and a heterocyclic group.
5. The preparation method according to claim 1, characterized in that The organic solvent is selected from one or two or more of N-methylpyrrolidone, N-ethylpyrrolidone, γ-valerolactone, γ-butyrolactone, N,N-dimethylformamide, N,N-dimethylacetamide and ethylene glycol dimethyl ether; and / or, The emulsifier is selected from one or two or more of sodium thiophenedicarboxylate, sodium succinate, sodium p-toluenesulfonate, lithium succinate, lithium p-toluenesulfonate and sodium dodecylsulfonate; and / or, The adhesive is selected from one or two or more of adhesive A, a mixture of adhesive A and PVDF, a mixture of adhesive A and copolyvinyl acetate, and a mixture of adhesive A and styrene-butadiene rubber; and / or, The nano ceramic particles are selected from one or two or more of aluminum oxide, magnesium oxide, zinc oxide, aluminum hydroxide and silicon dioxide; and / or, The particle size of the nano-ceramic particles is 300-500 nm; and / or, The weight ratio of the organic solvent, thiophene polyamide, nano-ceramic particles, emulsifier and adhesive is as follows: 6-30 parts of thiophene polyamide, 50-150 parts of organic solvent, 10-30 parts of nano-ceramic particles, 2-10 parts of emulsifier and 1-10 parts of adhesive; and / or, The first mixing conditions include: temperature of 15-30° C., time of 0.5-2 h, stirring rate of 150-300 rpm; and / or, The second mixing conditions include: temperature of 15-30° C., time of 1-3 h, and stirring rate of 150-300 rpm.
6. The preparation method according to claim 5, characterized in that The adhesive A is a polyarylene olefin carboxylate zinc salt composed of a first monomer, a second monomer and zinc hydroxide; and / or, The structural formula of the first monomer is shown in formula (a): ; The second monomer is butadiene.
7. The preparation method according to claim 5 or 6, characterized in that: The preparation method of the adhesive A comprises: 1) mixing a first monomer with zinc hydroxide in the presence of a first solvent, reacting the mixture, performing distillation under reduced pressure, and drying to obtain a zinc carboxylate salt of the first monomer; 2) mixing the zinc carboxylate salt of the first monomer obtained in step 1) with the second monomer in the presence of a second solvent, and then adding tetramethylethylenediamine and n-butyllithium to initiate polymerization; Wherein, the structural formula of the first monomer is shown as formula (a): ; The second monomer is butadiene.
8. The preparation method according to claim 7, characterized in that In step 1), the first solvent is a mixed solution of ethanol and water, with a mass ratio of ethanol to water of 1 to 2:1; and / or, In step 1), the mixing reaction conditions include: temperature of 40-60° C., time of 1-3 h; and / or, In step 1), the mass ratio of the first monomer to zinc hydroxide is 1:0.2-0.6; and / or, In step 2), the second solvent is tetrahydrofuran; and / or, In step 2), the mass ratio of the zinc salt of the carboxylate of the first monomer to the second monomer is 1:0.2-0.6; and / or, In step 2), the mixing conditions include: under anaerobic conditions, a stirring rate of 150-300 rpm and a temperature of 40-50° C.; and / or, In step 2), 5-10 mmol of tetramethylethylenediamine and 5-10 mmol of n-butyllithium are added per 100 g of butadiene; and / or, In step 2), the polymerization conditions include: under nitrogen atmosphere and / or argon atmosphere, the polymerization temperature is 30-60° C., and the time is 4-8 hours.
9. Application of a thiophene-based polyamide coating liquid in the preparation of a lithium battery separator, characterized in that: The thiophene-based polyamide coating liquid is a thiophene-based polyamide coating liquid prepared by the preparation method according to any one of claims 1 to 8.
10. A method for preparing a lithium battery separator, characterized in that: The preparation method comprises: coating a thiophene-based polyamide coating liquid on one side or both sides of a base film, performing coagulation bath extraction, and drying; wherein, The thiophene-based polyamide coating liquid is a thiophene-based polyamide coating liquid prepared by the preparation method according to any one of claims 1 to 8; The coating thickness is 0.5-4 μm; The base film is a polyethylene base film or a polypropylene base film.
Citation Information
Patent Citations
Diaphragm and preparation method thereof and lithium ion battery
CN108630867A
Method of making thermally-stable composite separators for lithium batteries
CN109935758A
Composite diaphragm slurry, preparation method thereof and battery diaphragm
CN113611983A
Lithium battery diaphragm and preparation method thereof
CN117423954A
Coating material, preparation method and application thereof, and lithium battery diaphragm
CN118027395A